BS EN IEC 61753-081-02. Fibre optic interconnecting devices and passive components. Performance standard. Part 081-02. Non-connectorized single-mode fibre optic middle-scale 1 x N DWDM devices for category C. Controlled environments (5th November 2021) - British Standards Institution,
No abstract available